2010
DOI: 10.1080/09593960903497773
|View full text |Cite
|
Sign up to set email alerts
|

Retailing in Europe: 20 years on

Abstract: “We are all familiar with the modern-day manager’s mantra that we live in times of great and constant change… We perceive our environment to be in constant flux because we only notice the things that do change ….Sure, important changes have taken place recently, but the truth is that stability and continuity also form the basis of our experience. In fact change has no meaning unless it is juxtaposed against continuity.” Huy & Minzberg (2003) This quote, paraphrased from a Sloan Management Review article on dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 86 publications
1
28
0
1
Order By: Relevance
“…Related research has also investigated the criteria consumers use when choosing a specific on-line retailer. Some have noted the role of trust and the increasing importance of the brand (Burt 2010;Büttner and Göritz 2008;Huang et al 2004;Mukherjee and Nath 2007;Pan, and Chiou, 2011) while others have identified operational issues as being an important determinant of loyalty. Policies and procedures relating to delivery times, item substitutions and product returns all have the potential to become sources of competitive advantage (Bonifield et al 2010;Chatterjee 2010;Doherty et al 1999;.…”
Section: E-commerce and Consumer Behaviourmentioning
confidence: 99%
“…Related research has also investigated the criteria consumers use when choosing a specific on-line retailer. Some have noted the role of trust and the increasing importance of the brand (Burt 2010;Büttner and Göritz 2008;Huang et al 2004;Mukherjee and Nath 2007;Pan, and Chiou, 2011) while others have identified operational issues as being an important determinant of loyalty. Policies and procedures relating to delivery times, item substitutions and product returns all have the potential to become sources of competitive advantage (Bonifield et al 2010;Chatterjee 2010;Doherty et al 1999;.…”
Section: E-commerce and Consumer Behaviourmentioning
confidence: 99%
“…One thing seems clear, in a retail environment in which brand is getting more, rather than less, important [Burt, 2010], it is likely that the big names will continue to dominate Internet retailing. At least in the immediate future, the majority of these big names will be established retailers who will continue to retain a very strong position within the electronic market-place.…”
Section: The Future Of Internet Retailingmentioning
confidence: 99%
“…El factor tiempo del consumidor influye en los cambios en las formas comerciales (Burt, 2010), siendo un factor crítico en sus estrategias de diferenciación (Inderst e Irmen, 2005). Abundantes estudios de sociología postulan nuevos comportamientos en el uso del tiempo de compra (Glorieux, Mestdag y Minnen, 2008;Neutens, Delafontaine, Schwanen Van de Weghe, 2012).…”
Section: La R Egulación De Horarios Comerciales Desde Una Visión Estrunclassified